Analisis Manajemen Risiko Konter Voucher dan Pulsa di Kecamatan Adiwerna, Tegal - Akbar Salafudin; Amirah (Indo Publishing, 2025)
This study analyzes risk management in voucher and mobile phone credit counter businesses in Adiwerna District, Tegal Regency, focusing on risk identification, evaluation, and management strategies. The research method employed a descriptive approach, using primary data obtained through a Google Form questionnaire from 30 respondents, consisting of counter owners, employees, and distributors. The data collected included risk assessments based on frequency, probability, and impact. The results indicate that the most frequent risks are price competition and digital services (73.3%), technical risks such as power and internet outages (66.7%), supply disruptions from providers (60%), internal fraud (50%), and seasonal demand fluctuations (46.7%). Using a probability-impact matrix, technical risks are ranked